2017
DOI: 10.1007/978-3-319-61194-5_22
|View full text |Cite
|
Sign up to set email alerts
|

Diversification as Part of a CSA Strategy: The Cases of Zambia and Malawi

Abstract: Climate variability, associated with farm-income variability, is recognized as one of the main drivers of livelihood diversification strategies in developing countries. In this chapter, we present a synthesis of two comprehensive studies from Zambia and Malawi on the drivers of diversification and its impacts on selected welfare outcomes with a specific attention to climatic variables and institutions. We use geo-referenced farm-household-level data merged with data on historical rainfall and temperature as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Other studies aim at discussing tools and measures for achieving CSA (Terdoo and Adekola, 2014). The literature is focused on diversification (Arslan et al , 2018), land management practices (Bell et al , 2018), agriculture intensification techniques (Campbell et al , 2014), social learning (Salvini et al , 2016b), sophisticated water management and irrigation practices (Olayide et al , 2016; Sikka et al , 2018; Imran et al , 2019), religiosity and community bounds (Davies et al , 2019), targeted investment (Branca et al , 2012) and gender empowerment (Bryan et al , 2017) as instruments for achieving CSA.…”
Section: Climate-smart Agriculture: a Brief Overviewmentioning
confidence: 99%
“…Other studies aim at discussing tools and measures for achieving CSA (Terdoo and Adekola, 2014). The literature is focused on diversification (Arslan et al , 2018), land management practices (Bell et al , 2018), agriculture intensification techniques (Campbell et al , 2014), social learning (Salvini et al , 2016b), sophisticated water management and irrigation practices (Olayide et al , 2016; Sikka et al , 2018; Imran et al , 2019), religiosity and community bounds (Davies et al , 2019), targeted investment (Branca et al , 2012) and gender empowerment (Bryan et al , 2017) as instruments for achieving CSA.…”
Section: Climate-smart Agriculture: a Brief Overviewmentioning
confidence: 99%
“…There was no age limit for diversification as indicated by the significant effect of age squared. Arslan et al (2017) on diversification as part of CSA strategy in Zambia and Malawi found out that long term variation in growing period rainfall was associated with increased crop, labor and income diversification in Malawi, and only associated with increased livestock diversification in Zambia. Maleheaded households had higher total labor diversification, indicating a potential barrier in labor markets for female headed households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in Zambia, nearly one in two household owns ruminants (2014 Zambian Rural Agricultural Livelihood Survey). Livestock income (including monogastrics) accounts for only 13% of the agricultural income but households owning livestock have higher total income on average (Arslan et al, 2018). This could be explained by the sales of animal products but also the addition of animal traction and manure.…”
Section: Generation Of Income At Households and National Levelmentioning
confidence: 99%